The effect of parental internal migration on children’s education: evidence from Indonesia - Anas, Yulia; Alisjahbana, Armida; Purnagunawan, Rd. Muhamad; Fahmi, Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study endeavors to investigate the effect of parental internal migration on children’s education. We focus on the children migrant parents, whether one or both parents who have migrated, and whether the children are co-migrants themselves or were left behind. Using cross section data of 372 individuals from Indonesian Family Live Survey (2014), the study employs the Two-Stage Least Squares method. The findings show that when the parent(s) migrate, the children’s school attendance is adversely affected. Further, migration causes poor school attendance in older children aged 13-14 years as compared to younger ones in the 6-12 years age category. In addition, children with migrant mothers tend to attend school more frequently than those with migrant fathers. Children left behind and cared for by grandparents were more frequently absent from school compared to children cared by their own fathers. Finally, mothers’ level of education positively improves children’s school attendance.